Seawater-based wastewater accelerates development of aerobic granular sludge: A laboratory proof-of-concept. (15th May 2017) - Li, Xiling; Luo, Jinghai; Guo, Gang; Mackey, Hamish R.; Hao, Tianwei; Chen, Guanghao
Abstract: This study aimed to develop an aerobic granular sludge process for the efficient treatment of highly saline wastewater and understand the granulation process in a seawater-based multi-ion matrix. Five identical sequencing batch airlift reactors (SBARs) are used to treat synthetic saline sewage with different proportions of real seawater (0%–100%). The results confirm that aerobic granular sludge can be successfully developed with various proportions of seawater up to 100% and show that seawater not only significantly accelerates granulation but also generates stronger granular structures than does freshwater. The increased presence of gel-forming alginate-like exopolysaccharides in the granules explains why a greater proportion of seawater leads to higher density and improves the cohesive strength of the granules. SEM-EDX analysis further revealed substantial presence of both Ca 2+ and Mg 2+ phosphate in the granule core as well as in the outer layers providing extra bridging forces in addition to alginate-like exopolysaccharides for accelerating the granule formation and maintaining the structure. It is hoped that this work could explore another approach for saline sewage treatment and bring some clues for the mystery of granulation mechanism. Graphical abstract: Highlights: A feasibility study of aerobic granular sludge treating seawater-based wastewater. Fast formation of granules was observed with mixing of seawater. Seawater increased abundant alginate-like EPS and its gelling properties. Three-stage seawater induced granulation mechanism is proposed.